Management Of Fractures In Parkinson's Disease - MAZHERUDDIN ALI KHAN,; V.R. SUJIT KUMAR, (International Journal of Pharma and Bio Sciences, 2012)
Parkinson's disease (PD) is a progressive neurodegenerative disorder affecting about 1 million people. Evidence indicates that Parkinson's disease patients are at a higher risk for low bone mineral density, which can contribute to increased fractures compared to healthy subjects. In fact, several risk factors of osteoporosis in patients with PD have been identified, including advanced stages of PD, low body mass index, inadequate sunlight exposure and decreased vitamin D levels. Some or all of these factors in conjunction with decreased immobilization that may occur with PD, can put patients at increased risks for fractures. Here in we report a case of distal humerus fracture with history of parkinsonism disease on tratment, which were managed with perioperative precautions in anaesthesia and orthopaedic point of view by open reduction and internal fixation by plating.